Clinical epidemiological characterization of patients with oral leukoplakia - Maurin Castelnaux Martínez; Ibisley Montoya Sánchez; Yuliet Serguera Batista; Rafael Medaldo Giraldo Moran; Antonio Pérez Rosabal (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The oral leukoplakia is clinically presented in multiple forms. At the moment it is considered that can be homogeneous or non homogeneous.  Objective: To characterize patients with oral leukoplakia according to selected variables.  Method:  A descriptive and cross-sectional study of 30 patients with leukoplakia was carried out, they were assisted in the Program of Detection of Oral Cancer service, belonging to the health area of Carlos Juan Finlay University Polyclinic in SongoLa Maya,Santiago de Cuba, during 2016. The following variables were analyzed: age, sex, skin color, risk factors, clinical forms presentation of leukoplakia, localization, number of lesions, time of nicotine addiction and malignant transformation. Results: The 45-64 age group, male sex and persons of mixed race prevailed.  The most affected anatomical localization was the residual alveolar edge. Most of those affected presented a single lesion with homogeneous clinical form, and any malignant transformation after their intervention. Nicotine addiction was the most prevalent risk factor.  Conclusions: The early detection of the oral complex lesions depends on the patient's examination on time.  An accurate diagnosis should be carried out to achieve a significant reduction of the morbidity and mortality and to increase cure and survival.